Supply Chain Management Practice and Its Impact on Performance of Humanitarian Relief Organization in Case of Gedeo Zone - Amsalu Sisay; Mezgebu Liku (Goodwood Publishing, 2022)
Purpose: The purpose of this study was to see how supply chain management practices affected humanitarian relief organizations in the Gedeo zone. Research methodology: The study used a mixed research approach, with respondents selected using a stratified proportionate technique from each organization's employees to disseminate a questionnaire and semi-structured interviews done using a purposeful sampling technique. Correlation and regression, as well as thematic analysis, were used in the analysis. Results: The finding of the study reveals that supplier integration, information sharing, postponement, and outsourcing affect humanitarian relief organizations’ performance positively in a statistically significant way. Limitations: The main limitation is that the study focused only on humanitarian relief organizations operating in the Gedeo zone. Contribution: Ethiopia experienced natural and human-made disasters such as (El Niño, flood, famine, war, communal conflict, etc) for decades. To reduce the threat of this, the Study suggests that supply chain management practice is a serious concern for many relief humanitarian organizations operating in the Gedeo zone.